Originally Posted by

**colby2152** *I probably went a roundabout and tediously long way of finding this, but the idea here is to abuse substitution and take advantage of the identity $\displaystyle sin^2(x)+cos^2(x)=1$...*

You have:

$\displaystyle sin(x)cos(y)=\frac{1}{4}$

$\displaystyle 3tan(x)=tan(y)$

Notice that...

$\displaystyle 3tan(x)=tan(y)$

$\displaystyle 3\frac{sin(x)}{cos(x)}=\frac{sin(y)}{cos(y)}$

$\displaystyle 3sin(x)cos(y)=sin(y)cos(x)$

$\displaystyle \frac{3}{4}=sin(y)cos(x)$

I guess that really didn't get us anywhere, did it?